Bicontinuous Nanoporous N‐doped Graphene for the Oxygen Reduction Reaction. (9th April 2014) - Ito, Yoshikazu; Qiu, H.‐J.; Fujita, Takeshi; Tanabe, Yoichi; Tanigaki, Katsumi; Chen, Mingwei
<x xml:space="preserve">Abstract</x> Bicontinuous nanoporous N‐doped graphene with tunable pore size is synthesized by nanoporous Ni‐based chemical vapor deposition. The novel 3D graphene material shows an outstanding catalytic activity towards the oxygen reduction reaction with a low onset potential of −0.08 V and a high kinetic current density of 8.2 mA cm−2 at −0.4 V. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>